Pengaruh BI Rate, Inflasi, NPF, BOPO, dan FDR Terhadap Profitabilitas Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia Periode 2019-2024 - Marshella Sukma; Any Eliza; Rosydalina Putri (STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
This study aims to analyze the effect of the BI Rate, inflation, Non-Performing Financing (NPF), Operating Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on profitability proxied by Return on Assets (ROA) in Islamic Rural Banks (BPRS) in Indonesia. This research employs a quantitative approach using multiple linear regression analysis. The data used are secondary data in the form of monthly aggregate industry data of BPRS in Indonesia, consisting of 72 observations during the research period. The results show that partially, the BI Rate and inflation have no significant effect on ROA. Meanwhile, NPF has a significant effect on ROA, BOPO has a negative and significant effect on ROA, and FDR has a positive and significant effect on ROA. Simultaneously, all independent variables significantly affect ROA. These findings indicate that BPRS profitability is more influenced by internal factors such as operational efficiency, financing quality, and the optimization of the intermediation function rather than external factors.